Learning Agility of Gen Z Employees in Navigating the Workforce: A Meta Analysis Study - Prayogi, Kukuh Ragil; Sari, Dwi Indah Permata; Nurmaseli, Tri (JURNAL JENDELA PENDIDIKAN, 2026)
This systematic literature review explores learning agility among Generation Z employees as they step into a workforce shaped by VUCA. Following PRISMA guidelines, we searched major databases including Google Scholar, ProQuest, SpringerLink, Taylor & Francis, Emerald Insight, and Sage Journals. Using keywords such as “learning agility,” “Generation Z,” and related terms, we selected eleven relevant articles published in English or Indonesian between 2020 and 2025. The findings show that Generation Z displays strong learning agility, seen in quick adaptation to digital tools, innovative behaviors, and resilience under pressure. At the same time, they face challenges from limited hands-on experience and interpersonal hurdles in early career stages. Learning agility stands out as a powerful predictor of work engagement, lower turnover intention, career adaptability, and overall performance. Organizations can strengthen this trait through supportive learning cultures, psychological safety, digital teaching methods, and tools that provide fast feedback. These insights highlight the strategic importance of nurturing learning agility to prepare for a workforce increasingly led by Generation Z and to build lasting organizational resilience.